Indole itself and its novel derivative affect PML cells proliferation via controlling the expression of cell cycle genes - Noroozi, Mojgan Karimabad; Mahmoodi, Mehd; Jafarzadeh, Abdollah; Darehkordi, Ali; Hajizadeh, Mohammad Reza; Khorramdelazad, Hossein; Sayadi, Ahmad Reza; Falahati-pour, Soudeh Khanamani; Hassanshahi, Gholamhossein (Cellular and Molecular Biology, 2019)
Recently the role of indole and pyran rings in carcinogenesis has been well studied. Here we studied the effects and the possible mechanisms of the action of basal indole (I3A) and its novel indole derivative (C19H15F3N2O) on inhibition of proliferation cells in acute promyelocytic leukemia NB4 cell line by examining the expression of cell cycle genes. We treated NB4 cells with concentration of C19H15F3N2O for 24-72 h. The MTT and PI/Annexin V examinations were employed for assessment of the proliferation and apoptosis of NB4 cells. Both of Cyclin D and P21 were detected by the Real-time PCR. The western blotting analysis was also performed to show the protein levels for P21. A difference was regarded significant if p-value was less than 0.05. MTT assay showed that 15.12-1000 µg/mL C19H15F3N2O caused a time and concentration-dependent inhibition of NB4 cell proliferation. Exposure to higher concentrations of C19H15F3N2O resulted in significantly increased apoptosis rate in NB4 cells. RT PCR showed that C19H15F3N2O has up-regulated the expression of P21 and down-regulated the expression of Cyclin D. Western blotting experiments also demonstrated that the P21 expression in C19H15F3N2O treated cells has significantly increased, where compared with either untreated control cells or I3A treated cells. This newly (C19H15F3N2O) was able to inhibit NB4 cells proliferation and causes apoptosis of these cells more than I3A, and these effects are probably facilitated via cell cycle arrest. C19H15F3N2O might probably be introduced as a promising organic therapeutic reagent against APL.